Lymphocyte transformation responses to phytohaemagglutinin and pokeweed mitogen in patients at differing stages of HIV infection: are they worth measuring?. Issue 9 (September 1993) - Bansal, A S; Moran, A; Potter, M; Taylor, R; Haeney, M R; Mandal, B K
Abstract : AIMS--To determine whether the routine measurement of lymphocyte transformation responses to mitogenic stimuli provide any information additional to that available from routine T cell CD4 and CD8 analysis in patients with HIV infection. METHODS--The case records of 197 immunologically investigated HIV seropositive patients were reviewed. The influence of disease stage on T lymphocyte subsets and lymphocyte transformation responses (LyTR) to phytohaemagglutinin (PHA) and Pokeweed mitogen was assessed. RESULTS--The median CD3 and CD4 counts and LyTR to PHA and Pokeweed mitogen were highest in patients with persistent generalised lymphadenopathy (PGL) and decreased progressively in the order: asymptomatic patients, those with ARC, those with AIDS. LyTR to PHA was preserved in over 70% of all patients, but the response to Pokeweed mitogen was depressed in 8% of patients with PGL, 34% of asymptomatic patients, 68% of those with ARC and 78% of those with AIDS. Subnormal values of both CD4 + T cells and LyTR to Pokeweed mitogen were more common in patients with ARC and AIDS (68%) than in those who were asymptomatic or had PGL (20%). CONCLUSIONS--CD4 T cell analysis and LyTR to Pokeweed mitogen, but not to PHA, both correlate with disease states in patients with HIV infection.